MORPHOMETRIC STUDY AND DENSITY OF Telescopium telescopium IN MANGROVE ECOSYSTEM OF SEKODI VILLAGE, BENGKALIS REGENCY, RIAU PROVINCE - Alka, M Abdi; Mulyadi, Aras; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted in August 2019 to determine the morphometric, density and sex ratio of Telescopium telescopium in Sekodi Village, Bengkalis Regency, Riau Province. Three sampling stations with three transects in each station were surveyed. The results showed that size of T. telescopium in areas far from community settlement were bigger than areas in the fishing boat lane and community settlement : 7.2 cm, 5.8 cm and 5.7 cm. The highest density was in areas community settlement and the lowest in the fishing boat lane. ANOVA test showed that there are no different of density between all the station. Sex ratio showed that T. telescopium was in the balance category (1:1)